Comparative analysis of the effects of different purification methods on the yield and purity of cow milk extracellular vesicles - Kankaanpää, Santeri; Nurmi, Markus; Lampimäki, Markus; Leskinen, Heidi; Nieminen, Anni; Samoylenko, Anatoliy; Vainio, Seppo J.; Mäkinen, Sari; Ahonen, Lauri; Kangasluoma, Juha; Petäjä, Tuukka; Viitala, Sirja (John Wiley & Sons, 2024)
Isolation of extracellular vesicles (EV) has been developing rapidly in parallel with the interest in EVs. However, commonly utilized protocols may not suit more challenging sample matrixes and could potentially yield suboptimal results. Knowing and assessing the pitfalls of isolation procedure to be used, should be involved to some extent for EV analytics. EVs in cow milk are of great interest due to their abundancy and large-scale availability as well as their cross-species bioavailability and possible use as drug carriers. However, the characteristics of milk EVs overlap with those of other milk components. This makes it difficult to isolate and study EVs individually. There exists also a lack of consensus for isolation methods. In this study, we demonstrated the differences between various differential centrifugation-based approaches for isolation of large quantities of EVs from cow milk. Samples were further purified with gradient centrifugation and size exclusion chromatography (SEC) and differences were analyzed. Quality measurements were conducted on multiple independent platforms. Particle analysis, electron microscopy and RNA analysis were used, to comprehensively characterize the isolated samples and to identify the limitations and possible sources of contamination in the EV isolation protocols. Vesicle concentration to protein ratio and RNA to protein ratios were observed to increase as samples were purified, suggesting co-isolation with major milk proteins in direct differential centrifugation protocols. We demonstrated a novel size assessment of vesicles using a particle mobility analyzer that matched the sizing using electron microscopy in contrast to commonly utilized nanoparticle tracking analysis. Based on the standards of the International Society for Extracellular Vesicles and the quick checklist of EV-Track.org for EV isolation, we emphasize the need for complete characterization and validation of the isolation protocol with all EV-related work to ensure the accuracy of results and allow further analytics and experiments.
Keywords: bioaerosol; extracellular vesicles; isolation protocol; milk; validation